The spring bear hunt isn't fair: end it - Rolston, Holmes, 1932-2025, author; The Denver Post, publisher (Colorado State University. Libraries, 1990)
Article arguing against spring bear hunting in the state of Colorado. In the spring bear hunt, especially with dogs, cubs are separated from their nursing mothers. If the sow is killed, the cubs starve. Bear hunting is seldom for meat, largely trophy and recreational hunting. Does Colorado wish to be a state where macho men shoot nursing mothers for fun?
Keywords: Colorado; spring; bear hunting; bear hunt